(untitled) (Indonesian Journal of Agrarian Law, 2026)
Disputes over land rights certificates are a problem that still often occurs in the practice of land law in Indonesia and shows the weak administrative system of land registration. To prove compliance with the concept of legal certainty and the social role of land, this study examines the judge’s reasons in Decision Number 237/Pdt.G/2024/PN.Smg. This normative legal research uses a legal approach and a case approach through a literature review of primary, secondary, and tertiary legal sources that are analyzed in a qualitative descriptive manner. The findings of the study show that although land rights certificates serve as strong evidence, they can still be revoked if there is an administrative or legal error. From Utrecht’s perspective, legal certainty demands clarity of rules and protection of the public from arbitrary government actions, which in this case have not been fully fulfilled due to the overlapping of certificates. According to Gustav Radbruch, the law must reflect certainty, justice, and utility. The judge’s decision shows an effort to balance the principle of legal certainty and the social function of land through examining the validity of the parties’ rights. However, the proof of physical data and the possession of land objects shows the complexity of resolving the dispute. The legal implications of this dispute include the administrative responsibility of the Land Office, the potential for civil lawsuits, and the possibility of criminal liability if there is an element of intentionality.